Implementasi Metode Cerita Islami dalam Menanamkan Moral Keagamaan Siswa di MIS Nurul Islam Seresam - Dessy Syofiyanti; Dian Purnomo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research refers to the initial survey that researchers find, that is, students who violate religious moral in schools, such as smoking at the time of lesson, steal the parking of the school, skip in the lesson hours, said rude and so on. Related to this problem, the purpose of this research is to solve this problem by embedding religious moral to students with Islamic story method. The study used qualitative methods with the research approach of Action class case study model Kurt Lewin. The instruments used are observation methods, interviews. Research informant of Madrasah (1 person), teacher (2 people), student (4 people). The data analysis techniques in this study use the Miles and Huberman models. The result of Islamic story method implementation in instilling religious moral in MIS Nurul Islam Seresam found that the moral changes of students occurring in school environment such as students often start to perform prayers at school, students begin to interact well with teachers and peers, students begin to show responsible attitude, discipline, and honest attitude. The advantages of the Islamic story method, the story can activate and awaken the students, emotionally directing the students well.